T43. SLEEP PROBLEMS RELATION TO COGNITIVE FUNCTIONING IN A TRANSDIAGNOSTIC SAMPLE OF PERSONS WITH PSYCHOTIC DISORDERS. (9th April 2019) - Savage, Christina; Andrea, Alexandra; Orth, Ryan; Bennett, Melanie; Blanchard, Jack
Abstract: Background: Sleep disturbances (e.g., insomnia, poor sleep quality and decreased sleep duration) are frequently endorsed by individuals with psychotic disorders (Bromundt et al., 2011; Holsten, 2011; Mulligan et al., 2016; Reeve, Sheaves, & Freeman, 2015). In fact, it is estimated that 30% to 80% of persons with psychotic disorders experience sleep disturbances (Freeman et al., 2009; Reeve et al., 2015; Xiang et al., 2009). Such high prevalence rates are concerning considering that sleep disturbances are associated with increased severity of psychiatric symptoms, decreased medication compliance, and declines in caregiver support and quality of a life (Afonso et al., 2014; Waters et al., 2011; Xiang et al., 2009). Although sleep disturbances have also been associated with deficits in overall cognitive functioning, working memory, long-term memory, executive functioning, and sustained attention in the general population (Gordon et al., 2017; Lowe et al., 2017), less is known about the association between sleep disturbances and cognition in populations with psychosis. A previous study showed that sleep disturbances were associated with poorer cognitive performance in persons with schizophrenia, which suggests that sleep disturbances may uniquely affect cognitive abilities (Bromundt et al., 2011). The current study will extend previous literature by examining the impact that sleep disturbances have on cognitive functioning in persons with psychotic disorders. Methods: The current study will examine the association between sleep disturbances and cognitive functioning in a transdiagnostic sample of persons with psychotic disorders. We will also investigate the relation between sleep impairments (e.g., daytime sleepiness, trouble concentrating, and problems staying awake) and cognitive functioning. We will use the short forms of the PROMIS-Sleep Disturbance and Sleep Impairment scales to assess problems with sleep over the past one week (Yu et al., 2012). We will administer the MATRICS Consensus Cognitive Battery (MCCB) to assess overall cognitive functioning and several cognitive domains (e.g., attention, working memory, and social cognition) (Nuechterlein et al., 2008). Results: Preliminary results (N = 59) indicated that increased sleep disturbances were associated with poorer speed of processing (r = -.28, p = .03) and poorer working memory (r = -.33, p = .01). Greater sleep impairment was also associated with poorer speed of processing (r = -.28, p = .03). In addition, sleep disturbances predicted speed of processing (b = -.51, SE = .23, pr2 = -.30, p = .03) and working memory (b = -.16., SE = .07, pr2 = -.31, p = .02) independent of common factors associated with cognition (i.e., race and education). Sleep impairment also predicted speed of processing (b= -.58., SE = .24, pr2 = -.31, p = .02) independent of race and education. We will conduct formal analyses with a larger N to further explore these and other associations. Discussion: Discussion will be included in the poster, after analyses with a larger sample are conducted.